ASSINATURAS GEOQUIMICAS DE SEDIMENTOS DE CORRENTE DOS TERRENOS PRECAMBRIANOS DO URUGUAY - Alba, Jose Maria Filippini (Geochimica Brasiliensis, 2022)
Geochemical data of Uruguayan crystalline terrains collected in the 80’s were recovery by the National Mining and Geology Directorate of Uruguay (DINAMIGE) in 2020 involving 32,000 soil and stream sediment samples analyzed for 22 elements (Ag, As, B, Ba, Be, Cd, Co, Cr, Cu, Fe, Mn, Mo, Nb, Ni, P, Pb, Sb, Sn, V, W, Y and Zn) by direct current plasma spectrometry. A set of 6755 samples of these data, more or less 21% of the total, were processed by multivariate statistical methods and geographic information system (GIS) procedures in this study aiming characterization of geochemical signatures derived from environmental and geological processes. Samples were classified as background, anomalies and outliers at the beginning, so geology classification with GIS and discriminant analysis allowed to define 14 signatures related to lithologies, hidrotermalism, sulphide occurrence, superficial or mixed processes. 84.4% of samples were considered background associated to the geological units, 8.9% of samples were undefined outliers, 2.6% of samples were interpreted as lithological anomalies, 3.8% of samples were associated to hidrothermalism, superficial processes or mixed models and only 0.3% of the samples were probably related to sulphide deposits occurrences.